Intensity of sub-syndromal anxiety symptoms in euthymic patients with bipolar disorder: A cross-sectional study - Jha, Alok; Koirala, Pooja; Aryal, Suman (Janaki Medical College Journal of Medical Science, 2026)
Background & Objectives: Evidence suggests that while the mood state improves and the patients achieve symptom recovery due to sub-syndrome anxiety symptoms functional recovery continues to be impaired and many of them don’t return to pre-morbid levels of functioning. This study was undertaken because such deficits are predictive of challenges in case management, treatment outcome. Materials and Methods: The cases were 40 consecutive euthymic bipolar patients who presented at OPD of Mental Hospital, Lagankhel. Equal number of matched controls were included in the study. Information regarding socio-demographic and clinical variables of study subjects was obtained through a semi-structured, self-designed questionnaire. Intensity of anxiety symptoms was assessed by the 21 Item Beck Anxiety Inventory. Results: In both the study groups, there was no significant difference in age, gender, marital status, residence, occupation and education. Regarding socioeconomic status, more individual in the normal healthy group were of middle socio-economic class (53%) compared to cases of euthymic BPAD (35%) group which were more of the low socio-economic class (65%). Intensity of Anxiety symptoms in the case group was significantly different from control group, suggesting some degree of persistent sub-syndromal anxiety symptoms in euthymic period. Conclusions: This study identified intensity of anxiety in euthymic patients of bipolar disorder. It would appear that even though the impact of medication upon generation of anxiety symptoms has yet to be fully elucidated, it is unlikely that medication factor fully account for that.